2018
DOI: 10.1111/jfr3.12491
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying damage contributions from convective and stratiform weather types: How well do precipitation and discharge data indicate the risk?

Abstract: Convective precipitation is intensifying in many regions, but potential implications of shifts in precipitation types on impacts have not been quantified. Furthermore, risk assessments often focus on rare extremes, but also more frequent hydro‐meteorological events burden private and public budgets. Here synoptic, hydrological, meteorological, and socio‐economic data are merged to analyse 25 years of damage claims in 480 Austrian municipalities. Exceedance probabilities of discharge and precipitation associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Climatological studies on severe convective weather events are still rare, but can reveal important information relevant to forecasting, such as their substantial contribution to total losses (e.g. Schroeer and Tye, 2019). For severe convective weather and hailstorms in particular, radar data provide one of the most important and reliable sources of observational data.…”
Section: Introductionmentioning
confidence: 99%
“…Climatological studies on severe convective weather events are still rare, but can reveal important information relevant to forecasting, such as their substantial contribution to total losses (e.g. Schroeer and Tye, 2019). For severe convective weather and hailstorms in particular, radar data provide one of the most important and reliable sources of observational data.…”
Section: Introductionmentioning
confidence: 99%
“…We selected heavy precipitation events observed with the WEGN during the extended summer (May-September) period in 2009-2014 (see also [11]). We first defined rain events with a minimum inter-event time of 6 h [64,65] and then selected the top 10% of the heaviest rainfall events. Finally, for the case studies, the three most extreme, small-scale, short-duration and the three most extreme, large-scale, long-duration events were selected (see also Figure A3 in Appendix A).…”
Section: Selection Of Precipitation Eventsmentioning
confidence: 99%
“…According to different precipitation types, precipitations can be categorized into convective and stratiform precipitation, as these two types of precipitation was thought to be formed by different precipitation growth mechanisms with very different mass and heating profiles (Dai, 2006; Houze, 1997; Schumacher et al, 2004). Several studies have reported historical convective and stratiform precipitation changes based on the observational data, and these results are beneficial for the understanding of cloud dynamics, cloud microphysics, distributions of precipitation latent heat release and their relationships with atmospheric circulations at the regional scales (Fu et al, 2017; Schroeer & Tye, 2018; Schumacher & Houze, 2006; Yu et al, 2010). For example, the convective precipitation responded more sensitively the changes in surface temperature than stratiform precipitation based on observational data, as it is influenced by both thermodynamic and dynamic processes (Berg et al, 2013; Loriaux et al, 2013).…”
Section: Introductionmentioning
confidence: 99%